miR-22-3p as a potential biomarker for coronary artery disease based on integrated bioinformatics analysis - Zhang, Minghua; Hu, Yan; Li, Haoda; Guo, Xiaozi; Zhong, Junhui; He, Sha (Frontiers in Genetics, 2022)
Background：As a common cardiovascular disease, coronary artery disease (CAD) has attracted worldwide attention for its high morbidity and mortality. Recent studies discovered that abnormal expression of microRNAs is effective for the diagnosis and process of CAD. However, the potential relationship between microRNAs and CAD remains elusive. Methods：To identify microRNAs involved in the CAD, the microarray datasets GSE105449 and GSE28858 were directly downloaded from the gene expression omnibus (GEO). Subsequently, target gene prediction and enrichment analyses were performed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Results：There were 9 differentially expressed microRNAs of CAD patients compared to the expressed microRNAs of the controls. A total of 352 genes were predicted and subjected to GO analysis, which showed that DEGs were mainly associated with axon guidance, neuron projection guidance, neuron to neuron synapse, and postsynaptic density. According to the KEGG pathway analysis, the most enriched pathways were those involved in transcriptional misregulation in cancer, growth hormone synthesis, secretion and action, endocrine resistance, axon guidance and Cushing syndrome. Pathways analysis were mainly involved in HIPPO and prion disease signaling pathways. Furthermore, constructing a ceRNA interaction network centered on miR-22-3p, a total of eight related transcription factors in the cardiovascular system. ROC curve analysis suggested that miR-22-3p may be a better predictor of coronary artery disease. Conclusion: The results indicated that miR-22-3p might play the part in the Pathophysiological processes of CAD. Our study may provide useful information that miR-22-3p might as specific biomarkers for the diagnosis of CAD.